Distinct Interplay Between Atrophy and Hypometabolism in Alzheimer's Versus Semantic Dementia. (13th April 2018) - Bejanin, Alexandre; La Joie, Renaud; Landeau, Brigitte; Belliard, Serge; de La Sayette, Vincent; Eustache, Francis; Desgranges, Béatrice; Chételat, Gaël
Abstract: Multimodal neuroimaging analyses offer additional information beyond that provided by each neuroimaging modality. Thus, direct comparisons and correlations between neuroimaging modalities allow revealing disease-specific topographic relationships. Here, we compared the topographic discrepancies between atrophy and hypometabolism in two neurodegenerative diseases characterized by distinct pathological processes, namely Alzheimer's disease (AD) versus semantic dementia (SD), to unravel their specific influence on local and global brain structure–function relationships. We found that intermodality topographic discrepancies clearly distinguished the two patient groups: AD showed marked discrepancies between both alterations, with greater hypometabolism than atrophy in large posterior associative neocortical regions, while SD showed more topographic consistency between atrophy and hypometabolism across brain regions. These findings likely reflect the multiple pathologies versus the relatively unitary pathological process underlying AD versus SD respectively. Our results evidence that multimodal neuroimaging-derived indexes can provide clinically relevant information to discriminate the two diseases, and potentially reveal distinct neuropathological processes.